Pengaruh Partisipasi Penyusunan Anggaran terhadap Kinerja Instansi Pemerintah dengan Komitmen Organisasi sebagai Variabel Moderating - Iin Indarti; Anton Anton; B Eko Setya Wati (Jurnal Ilmiah Aset, 2017)
This study aimed to determine the influence of budgeting participation on performance of Government Institutions with organizational commitment as a moderating variable. The population in this study were civil servants of Electoral Commission of Central Java and Semarang City amounted to 51 people. The samples in this study were employees who participated in the budget amounted to 40 people. The sampling technique used was purposive sampling technique. The technique of primary data collection was conducted by spreading the questionnaire to the Electoral Commission of Central Java and Semarang City. The results of this study were (1) the participation of budgeting had positive influence on performance of government institutions (2) organizational commitment didn’t empower the influence of budgeting participation on performance of government institutions.